Comments on Professor Forrester's“Industrial Dynamics—After The First Decade” - Ansoff, H. Igor; Slevin, Dennis P. (Management Science, 1968)
Comments on Forrester, J. W. 1968. Industrial dynamics—After the first decade. Management Sci. 14(7, March) 398–415.